2015
DOI: 10.7314/apjcp.2015.16.14.5883
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with a Small Synthetic Compound, KMU-193, induces Apoptosis in A549 Human Lung Carcinoma Cells through p53 Up-Regulation

Abstract: Despite recent advances in therapeutic strategies for lung cancer, mortality still is increasing. In the present study, we investigated the anti-cancer effects of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…In agreement with our results, Xu and his coworkers have identified that Pb-induced apoptosis can be mediated through an increase of P53 in mice PC 12 cells (Xu et al 2006(Xu et al , 2008. Moreover, Tousson et al (2011) reported that Pb-exposure causes a significant increase in apoptotic P53 protein in rabbit liver tissues (Tousson et al 2011) and that P53 knockdown attenuates apoptosis induction (Jung et al 2012;Choi et al 2015;Liu et al 2015). These observations not only indicate that Pb is a strong trigger for apoptosis but also strongly suggest that P53 plays a key role in Pb-induced apoptosis.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our results, Xu and his coworkers have identified that Pb-induced apoptosis can be mediated through an increase of P53 in mice PC 12 cells (Xu et al 2006(Xu et al , 2008. Moreover, Tousson et al (2011) reported that Pb-exposure causes a significant increase in apoptotic P53 protein in rabbit liver tissues (Tousson et al 2011) and that P53 knockdown attenuates apoptosis induction (Jung et al 2012;Choi et al 2015;Liu et al 2015). These observations not only indicate that Pb is a strong trigger for apoptosis but also strongly suggest that P53 plays a key role in Pb-induced apoptosis.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies revealed that p53/p21 pathway mediates lung cancer A549 cells apoptosis. 27 , 28 Our Western blot assay showed that the levels of p53 and p21Cip1/Waf1 were significantly augmented in the atracurium group compared with the control group ( Figure 5D and E ), suggesting that apoptotic effects on A549 cells are largely mediated through p53-dependent pathways.…”
Section: Discussionmentioning
confidence: 93%
“…p53 is a tumor-suppressor and has been shown to mediate a variety of antiproliferative and/or pro-apoptotic processes in response to diverse forms of cellular stress (27,28). Studies have recently demonstrated that apoptosis of the A549 cells is accompanied by p53 upregulation (27,29) and siRNA-mediated p53 knockdown markedly reduces apoptosis of A549 cells (27), suggesting a role of p53 upregulation in cell apoptosis. It is thus speculative that an increase in phosphorylated p53 may further become a part of the aRVS extract-mediated anticancer effects on A549 cells.…”
Section: Discussionmentioning
confidence: 99%